Musical Instruments In Renaissance Paintings - Simion Aurelia (Sciendo, 2021)
Art, the language of ideas and concepts, comprises a multitude of means of manifestation through sound, word, color, gesture, etc., between which there is often an interconnection. This article highlights some aspects of the aesthetics of the Renaissance period in which artists, starting from Italy, focused on realism and human emotion in art, but also on the interconnection between two arts - painting and music. In this sense, we turned our attention to identifying the symbolic role of the musical instruments of that period represented in paintings by some notable masters from Italy, Flanders and Germany.